Thinking Outside the Box—Novel Antibacterials To Tackle the Resistance Crisis. Issue 44 (11th October 2018) - Lakemeyer, Markus; Zhao, Weining; Mandl, Franziska A.; Hammann, Peter; Sieber, Stephan A.
Abstract: The public view on antibiotics as reliable medicines changed when reports about "resistant superbugs" appeared in the news. While reasons for this resistance development are easily spotted, solutions for re‐establishing effective antibiotics are still in their infancy. This Review encompasses several aspects of the antibiotic development pipeline from very early strategies to mature drugs. An interdisciplinary overview is given of methods suitable for mining novel antibiotics and strategies discussed to unravel their modes of action. Select examples of antibiotics recently identified by using these platforms not only illustrate the efficiency of these measures, but also highlight promising clinical candidates with therapeutic potential. Furthermore, the concept of molecules that disarm pathogens by addressing gatekeepers of virulence will be covered. The Review concludes with an evaluation of antibacterials currently in clinical development. Overall, this Review aims to connect select innovative antimicrobial approaches to stimulate interdisciplinary partnerships between chemists from academia and industry. Abstract : Fit for the future : The discovery of novel antibacterials is a highly interdisciplinary field which relies on input from various research areas. This Review encompasses several aspects of antibiotic development—from very early strategies to mature drugs in clinical trials. An overview is given of methods suitable for mining novel antibacterials and for the elucidation of their bacterial targets.